2012
DOI: 10.1128/aem.05157-11
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Host-Associated Bacteroidales Cells and Their Relationship with Enterococcus spp., Campylobacter jejuni, Salmonella enterica Serovar Typhimurium, and Adenovirus in Freshwater Microcosms as Measured by Propidium Monoazide-Quantitative PCR

Abstract: The ideal host-associated genetic fecal marker would be capable of predicting the presence of specific pathogens of concern. Flowthrough freshwater microcosms containing mixed feces and inocula of the pathogens Campylobacter jejuni, Salmonella enterica serovar Typhimurium, and adenovirus were placed at ambient temperature in the presence and absence of diurnal sunlight. The total Enterococcus DNA increased during the early periods (23 h) under sunlight exposure, even though cultivable Enterococcus and DNA in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 50 publications
3
60
0
Order By: Relevance
“…These findings emphasize the potential for using Bacteroidales marker for MST field studies. Bae and Wuertz [118] reported similar decay of Bacteroidales and Campylobacter cells exposed to sunlight. DNA from Bacteroides and pathogens such as Campylobacter spp., Salmonella spp., and adenoviruses decayed at comparable rates.…”
Section: Decay Of Human-specific Bacteroides Markers In Environmentalmentioning
confidence: 63%
“…These findings emphasize the potential for using Bacteroidales marker for MST field studies. Bae and Wuertz [118] reported similar decay of Bacteroidales and Campylobacter cells exposed to sunlight. DNA from Bacteroides and pathogens such as Campylobacter spp., Salmonella spp., and adenoviruses decayed at comparable rates.…”
Section: Decay Of Human-specific Bacteroides Markers In Environmentalmentioning
confidence: 63%
“…Some researchers report no significant difference in the decay of Bacteroides hostassociated genetic markers with or without sunlight exposure (24,25,31), while others note that decay under light conditions is significantly faster (32). It has also been suggested that exposure to sunlight is more detrimental to live cells (as assessed by propidium monoazide treatment) than it is to DNA, implying that the disagreement in the reported literature may be due to the physiological state rather than to a direct effect of sunlight (33). Considerably less is known about the impact of biotic interactions (e.g., predation, competition, and viral lysis); existing laboratory-scale and mesocosm studies suggest that these interactions can play an important role (23,24,26,28), but this assertion has not been confirmed in field studies.…”
mentioning
confidence: 69%
“…There are a wide variety of bacterial genera, groups, and species, viruses, and bacteriophages that have been used or proposed for use as indicator microorganisms (3,(7)(8)(9). Coliforms, either total or fecal, are a common choice of indicator organism.…”
mentioning
confidence: 99%